Self-efficacy and writing performance : an investigation on trainee teachers / Norshilawani Shahidan - Shahidan, Norshilawani (2013)
Numerous research has been done in investigating the impact of self-efficacy in academic settings. Nevertheless, this issue has not received as much concern in the context of Malaysia especially in the issue that deals with specific language skills such as writing skills. Thus, this study was conducted in looking at the level of writing selfefficacy and its relationship with actual writing performance and the possible factors that affect the respondents' writing self-efficacy. Writing self-efficacy has been emphasized to impact students' writing performance (Kahraman, 2012; Erkan and Saban, 2011) and this shows the importance of this construct in academic settings. This study adapted primarily quantitative data which was later substantiated by qualitative data to certify data reliability. This study involved the population of 43 trainee teachers from International Islamic University College of Selangor (KUIS) who were taking Diploma in Teaching (Teaching English as a Second Language). This study applied several methods in collecting the sources of evidence namely questionnaires distribution, writing test and focus-group interview. The findings of this study illustrated that the trainee teachers possessed moderate level of writing self-efficacy and there was no relationship between writing self-efficacy and writing performance. Furthermore, it was also demonstrated from the findings that there was no significant difference in writing self-efficacy for trainee teachers from different semesters. Finally, majority of the students chose vicarious experience as the factor that affected their writing self-efficacy the most. This study was an attempt to investigate the issue of writing self-efficacy in Malaysian context which is hoped will lead to the improvement of teacher training programs as it can probably lead to the improvement of instructions on the trainers' side by looking at the factors affecting writing self-efficacy and the improvement of proficiency level particularly for writing skills on the trainees' side to maximize the impact of writing self-efficacy.